Intramolecular cyclization in hyperbranched star copolymers via one-pot Am+Bn+C1 step-growth polymerization resulting in decreased cyclic defect. (15th July 2021) - Ban, Qingfu; Li, Yan; Qin, Yusheng; Zheng, Yaochen; Kong, Jie
Graphical abstract: Am +Bn +C1 hyperbranched star copolymers with multidodal molecular weight distribution produced from one-pot one-batch process exhibit an increased influence of number of maromolecules and decreased influence of intramolecular cyclization on the number raito of monomeric structural units contrast Am +Bn hyperbranched polymers so as to regulate hyperbranched star topology for an unexpected aqueous self-assembly. Highlights: One-pot one-batch synthesis of Am+Bn+C1 hyperbranched star copolymers. A convenient expression of NA /NB for the analysis of intramolecular cyclization. Effect of intramolecular cyclization and number of macromolecules on topology. Abstract: Hyperbranched star copolymers are important soft materials that have been employed for aqueous self-assembly and bioapplication, but their one-pot one-batch synthesis strategy and relevant topology are rarely discussed. In this contribution, we produce hyperbranched star poly(vinyl ether ester)s (mPEG- hb -PVEEs) amphiphiles with multimodal molecular weight distribution via one-pot one-batch Am+Bn+C1 (m ≥ 2, n ≥ 3) step-growth polymerization. Based on the topological analysis of these hyperbranched star copolymers, a convenient expression of the number ratio of monomeric structural units (NA /NB ) is deduced to describe the cyclic defect of intramolecular cyclization only by using proton nuclear magnetic resonance spectroscopy. The introduction of long-chain terminators and the change in the molar feed ratio of A2 :B3 :C1 considerably affect the NA /NB so as to give rise to increased influence of number of macromolecules and decreased influence of intramolecular cyclization, which are then responsible for an aqueous self-assembly behavior of mPEG- hb -PVEEs amphiphiles. Overall, this study opens new possibilities for the precise description of intramolecular cyclization and controllable synthesis of hyperbranched star copolymers via one-pot Am+Bn+C1 step-growth polymerization.